FACTORS ASSOCIATED WITH RATIONALITY OF ANTIMALARIA PRESCRIPTION IN PAPUA PROVINCE - Irene Sondang Lingga; Sarhana Sarhana Rassya Aulyah Said; Dina Ayomi; Rusnaeni Rusnaeni; Elsye Gunawan; Nur Fadilah Bakri; Elfride Irawati Sianturi (Jurnal Farmasi Sains dan Praktis, 2023)
Malaria remains a leading cause of death in Papua and combination of Dihydroartemisin -Piperaquine (DHP) and Primaquine (PQ) is recommended treatment to replace chloroquine out since chloroquine resistance present. Moreover, awareness of rational prescription and adherence may be the first priority in malaria treatment in preventing death and resistance in Papua. This study aimed to assess the rationality of antimalaria prescription in the public and private sectors of Papua Province. This cross-sectional study was conducted. Overall, 571 prescriptions were included in this study and more than half of prescription was rational (65%). This study was predominantly female (65%). More than half was diagnosed by P. falciparum (54%), using referred using the public hospital for treatment (54%) and self-identified as Papuan (50%). According to type of malaria, incorrect of prescription DHP and PQ were 20% and 18%, respectively. The multiple logistic regression model showed that female was significantly associated to receive irrational of prescriptions than males (OR = 1.549; 95% CI =1.004-2.389). Participants who had P. falciparum increased the likelihood of irrational of prescriptions (OR= 1.641; 95% CI =1.144-2.355). There is a need to have a continuum strategy to improve access and utilization of malaria case management in both public and private health facilities. Inequality gender based on prescribers needs to be investigated. Competence improvement among healthcare providers needs to be a priority to prevent antimalarial resistance.